Thermal-Microstructural Analysis of Anodic and Electrolytic Copper Solidification: Simulation and Experimental Validation - Cruchaga-Ssa., M (2011)
This work analyzes the solidification process of anodic and electrolytic copper. The aim of this study is to perform an experimental validation of numerical results computed using a proposed thermal formulation including microstructural evolution. To this end, a set of experiments is carried out testing primary and eutectic phase formation in copper. To evaluate the formation of different microstructural phases, anodic copper (99.80 pct purity, approximately) and electrolytic copper (99.99 pct purity, approximately) are used. Primary and eutectic phases evolve in anodic copper; meanwhile, only a primary phase is obtained in electrolytic copper. The effect of heat extraction conditions is evaluated using sand, graphite, and steel molds to promote different cooling rates. The proposed microstructural model takes into account nucleation and grain growth laws based on thermal undercooling together with microstructural evolution. The primary copper evolution model is based on solute diffusion at the grain scale and on the dendrite top-growing kinetic; meanwhile, the eutectic evolution is assumed proportional to the copper initial composition and eutectic undercooling. The corresponding numerical formulation is solved in the framework of the finite-element method. Finally, the computed temperature histories and final values for the grain density and radius, including primary or dendritic phase and eutectic solid volumetric fractions, are all compared and validated with the experimental measurements. © 2011 The Minerals, Metals & Materials Society and ASM International.